2021
DOI: 10.1111/1471-0528.16625
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiac arrest: a retrospective analysis

Abstract: Objectives To describe the characteristics and factors which may influence the maternal outcomes of maternal cardiac arrest (MCA). Design Retrospective analysis of cases. Setting China. Population or sample A total of 61 MCA patients admitted or transferred to The Third Affiliated Hospital of Guangzhou Medical University from January 2000 to December 2019. Methods Clinical data for MCA were analysed retrospectively. The indicators included maternal age; BMI; gestational age; antenatal examination; income; MCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…One study showed that chorioamnionitis was found in 4.9% of maternal cardiac arrests, and sepsis from any source was present in 8.8% of maternal cardiac arrests. 8 Unfortunately, 40% of cardiac arrests related to sepsis result in death. 9 Ampicillin and gentamicin are standard therapies for chorioamnionitis.…”
Section: Maternal Sepsis and Cardiac Arrestmentioning
confidence: 99%
“…One study showed that chorioamnionitis was found in 4.9% of maternal cardiac arrests, and sepsis from any source was present in 8.8% of maternal cardiac arrests. 8 Unfortunately, 40% of cardiac arrests related to sepsis result in death. 9 Ampicillin and gentamicin are standard therapies for chorioamnionitis.…”
Section: Maternal Sepsis and Cardiac Arrestmentioning
confidence: 99%
“…L'arrêt cardiaque chez la mère est une complication rare de la grossesse et du postpartum. Une étude a montré que la chorio amnionite était présente dans 4,9 % et la septicémie, quelle qu'en soit la source, dans 8,8 % des arrêts cardiaques maternels 8 . Malheureusement, 40 % des arrêts cardiaques liés à la septicé mie sont fatals 9 .…”
Section: Septicémie Et Arrêt Cardiaque Chez La Mèreunclassified
“…In their data, Liu et al have reported very high survival (77.8%) among those who underwent PMCS, in contrast to most of the available literature. 1,2 We congratulate the authors on this. However, we feel that discussing more details -in particular the time-frame between cardiac arrest and delivery -would help those with less expertise, should such an unfortunate event ever occur in their practice.…”
mentioning
confidence: 96%
“…Dear Dr Papageorghiou, We read the retrospective data on maternal cardiac arrest by Liu et al 1 with a lot of interest. This was especially intriguing to us, as maternal cardiac arrest is not well-reported from resource-limited countries like India.…”
mentioning
confidence: 99%
See 1 more Smart Citation